THE DIFFERENCE OF IoS AND ANDROID USAGE - Rachel Margaretha Siburian; Ripta Permata Nuary (Jurnal Darma Agung, 2019)
This research aims at comparing the quality, price, users and interest of the society on IoS and Android. This research also directs readers to be more careful in choosing a product, wiser in comparing products. Both of IoS and Android products are good enough but it would be nice to choose the better one. The reason for conducting this research is to facilitate consumers in choosing products. The method research used is qualitative with natural observers, and the use of questionnaires to obtain data from several communities in the Pos Indonesia Polytechnic Campus.